Diagnostico situacional turístico de la parroquia rural Fundochamba del cantón Quilanga, provincia de Loja - Correa Imaicela, Irrael Benito (2015)
Tourism is a social activity that has had a rapid progress in recent years, activity considered as a space for leisure and entertainment only, has become the enabling environment for personal cultural and social growth, which in turn contributes positively the development and progress of peoples, it is the medium that involves various sectors that until recently were thought opposites. While in rural areas the poor management that has been applied for a long time, showing the poor utilization of tourism resources without regard to their deterioration, before this problem, the World Tourism Organization proposes the conversion of tourism is observed an activity that has as its main objective the economic, social and environmental balance, in other words implement sustainable tourism through proper and timely planning of destinations. That is why this study is based on the manual for Local tourist diagnosis that their content is described as the stage of the planning process which establishes and assesses the status of a destination at a certain time, also it constitutes direct source information that allows decisions about future strategies and the tool that will allow assessment of the success or failure of plans, projects and programs. The project "tourist situational analysis of rural parish Fundochamba Quilanga Canton, province of Loja" is an initiative developed in order to assist the effective progress of the tourist activity in that sector. By applying two surveys in the place of study, it was found the absence of a tourist diagnosis and various shortcomings that prevent their development, that is why achievable targets to leverage resources and establish strategies of progress was raised. The overall objective of this work was: Identify alternatives for tourism development in the rural parish Fundochamba Quilanga Canton of the Province of Loja, through a tourist diagnosis for it was implemented three specific objectives: First, to characterize the current situation of tourism in the rural parish Fundochamba with its opportunities and limitations, second, to determine the composition of the tourism supply and demand; and third, to design strategies for tourism development in the sector. To do this research methods as applied scientific research by providing a logical sequence, the analytical method for the decomposition of the internal components of the tourism system characteristics, the synthetic method to order and rebuild everything broken and bibliographic providing all conceptual references. Besides it was essential to use some investigative techniques such as direct observation where we proceeded to develop an inventory of tourist sites in the rural parish Fundochamba, using the methodology of the Ministry of Tourism and technical instruments of pressure; the interview was aimed at gathering the necessary information from the study site, by applying the format recommended in the manual for local tourist diagnosis of Ricaurte Carla Quijano; for demand analysis survey was applied in the rural parish Fundochamba to learn from its people the importance given to tourism resources of the area. Finally it should be emphasized that in designing the tourism development strategies MARPP technique that consisted of a participatory workshop where stakeholders participated in the design of a SWOT matrix and identified possible programs and projects was used. The results are checked by establishing baseline allowed to develop three specific objectives; It was able to integrate the components of the tourism system collecting necessary information; determining the offer demonstrating the tourism potential sites identified for Class I, such as Plaza del Inca, Cerro guinea pigs, Piedra Grande and Central Square and Parish Church, also tourism demand states where identified tourist profile; designing strategies led to the creation of programs and projects that provide a better quality of life for the direct and indirect actors involved in tourism. Culminating with the tourist situational analysis , was considered among the conclusions that the rural parish Fundochamba has a low potential for tourism, also the services and tourism in the parish are zero, since there are no facilities that provide lodging, food and information on the options that own the place . Also defined as the main weakness of the sector is the lack of signage and evaluation of tourism resources which recommends the relevant authorities to implement the conservation and preservation of resources and likewise use and disseminate, which allow local economic development while improving the quality of life of its inhabitants.